2005
DOI: 10.1002/ange.200501399
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Chemoselective 6′‐N‐Derivatization of Aminoglycosides: Bisubstrate Inhibitors as Probes To Study Aminoglycoside 6′‐N‐Acetyltransferases

Abstract: Einfach zu komplexen nanomolaren Inhibitoren: Aminoglycosid‐Coenzym‐A‐Derivate wurden durch eine effiziente regioselektive 6′‐N‐Modifizierung von Aminoglycosiden hergestellt (siehe Schema). Diese Bisubstrate sind fest bindende kompetitive Inhibitoren der Aminoglycosid‐6′‐N‐Acetyltransferase, eines an der Antibiotikaresistenz beteiligten Enzyms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…242 These bisubstrate analogues mimic the proposed tetrahedral intermediate, resulting in structures with amide-based aminoglycoside-CoA linkages. The compounds detailed in Reference 242 provide insight into the reactions of acetyltransferases based on knowledge of their structures, however, more detailed kinetic and thermodynamic investigations are required to determine the effect of these inhibitors on the cooperative mechanism.…”
Section: Aminoglycoside N-(6’)-acetyltransferase IImentioning
confidence: 93%
See 2 more Smart Citations
“…242 These bisubstrate analogues mimic the proposed tetrahedral intermediate, resulting in structures with amide-based aminoglycoside-CoA linkages. The compounds detailed in Reference 242 provide insight into the reactions of acetyltransferases based on knowledge of their structures, however, more detailed kinetic and thermodynamic investigations are required to determine the effect of these inhibitors on the cooperative mechanism.…”
Section: Aminoglycoside N-(6’)-acetyltransferase IImentioning
confidence: 93%
“…239,242 The 2003 report of Draker et al describes partial competitive inhibition of AAC(6’)-Ii by desulfo-CoA, expressed as K is = α K i , where α is the change in K m when the inhibitor is bound to the ES complex. At varied concentrations of AcCoA, K is is reported to be 6.58 ± 2.18 μM.…”
Section: Aminoglycoside N-(6’)-acetyltransferase IImentioning
confidence: 99%
See 1 more Smart Citation
“…Further research led to synthesis of other bisubstrates of smaller size by using truncated aminoglycosides or CoA. One of the compounds, showed a synergistic effect with kanamycin on the growth of E. faecium harboring AAC(6′)-Ii, an enzyme that catalyzes acetylation through an ordered mechanism (Draker et al, 2003; Gao et al, 2005; Gao et al, 2006). Subsequent kinetic and structural studies using AAC(6′)-Iy, which binds the substrates on a random manner, as a target found that the bisubstrates analyzed bind to this enzyme with much lower affinity (Magalhaes et al, 2008).…”
Section: Strategies To Overcome the Effect Of Aminoglycoside Modifmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] During the past two decades, significant efforts have been devoted to the design of new aminoglycoside antibiotics that are immune to inactivation [18] and also to the preparation of specific enzymatic inhibitors that could be co-administered in tandem with natural antibiotics. [19] Unfortunately, few examples of successful designs have been reported and none of them has entered clinical use, thus reflecting our limited understanding of the basic thermodynamic, kinetic and mechanistic features of the drug inactivation process. Evidently, medicinal chemistry efforts would greatly benefit from an insightful knowledge of the basic properties of aminoglycoside-modifying enzymes.…”
Section: Introductionmentioning
confidence: 99%